Nowcasting Bosnia and Herzegovina GDP in Real Time - Antonio Musa (Graduate Institute of International and Development Studies, 2022)
The aim of this paper is to evaluate current quarterly nowcasts of the gross domestic product in Bosnia and Herzegovina based on the flow of available monthly economic indicators that are available during the same quarter. The nowcasting performance indicates that it is worthwhile to include a broad group of forecasting models based on the different methodologies. In addition to the models, the choice of the variables and measurement of the loss function in evaluating nowcasting performance are the core of nowcasting. In a time marked by pandemic of corona virus and war in Ukraine, nowcasting models have more profound role than more structural models. The high variance of the specific nowcasting model influences the use of the results of combinations of many models. Using a comprehensive method for preselection of variables and by using the other combination methods, the forecasting errors are lower, even in times of high uncertainty.
Keywords: E17; E66; C52; C55; O11; 330; Nowcasting; short-term forecasting; uncertainty; pandemic